Bringing Back the Jobs Lost to Covid-19: The Role of Fiscal Policy - CHRISTIAN BREDEMEIER; FALKO JUESSEN; ROLAND WINKLER (Journal of Money, Credit and Banking, 2022)
Covid-19 induced job losses occurred predominantly in industries with intensive worker–client interaction as well as in pink-collar and blue-collar occupations. We study the ability of fiscal policy to stabilize employment by occupation and industry during the Covid-19 crisis. We use a multisector, multioccupation macro-economic model and investigate different fiscal-policy instruments that help the economy recover faster. We show that fiscal stimuli foster job growth for hard-hit pink-collar workers, whereas stimulating blue-collar job creation is more challenging. Only a cut in labor income taxes generates a substantial number of blue-collar~jobs.
Keywords: 330; Covid-19; fiscal policy; composition of employment; occupations; industries; heterogeneity